2015
DOI: 10.1097/wno.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates and Predictors of Functional Recovery After Chiasmal Decompression

Abstract: Background The intrinsic abilities and limits of the nervous system to repair itself after damage may be assessed using a model of optic chiasmal compression, prior to and following a corrective surgical procedure. Methods Visual fields (VFs), multi-focal visual evoked potentials (mfVEP), retinal nerve fiber layer (RNFL) thickness and diffusion tensor imaging (DTI) were used to evaluate a patient before and after removal of a meningioma compressing the chiasm. Normally-sighted individuals served as controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Table 1 gives a summary of existing tractography-based RGVP studies to describe the current state of the art in terms of the fiber tracking methods being used, among which the standard diffusion tensor imaging (DTI) tractography and more advanced methods such as those using constrained spherical deconvolution (CSD) and generalized Q-sampling imaging (GQI) are most widely used. While these studies have shown highly promising T A B L E 1 Summary of published tractography studies of the RGVP and its subregions, organized according to the fiber reconstruction methods employed and the anatomical region studied OT Backner et al (2018), Frezzotti, Giorgio, Toto, De Leucio, andDe Stefano (2016), Glick-Shames, Backner, Bick, Raz, and Levin (2019), Hoffmann et al (2012), Levin, Dumoulin, Winawer, Dougherty, and Wandell (2010), Malania, Konrad, Jägle, Werner, and Greenlee (2017), Maleki, Becerra, Upadhyay, Burstein, and Borsook (2012), Ogawa et al (2014, Raz, Bick, Klistorner, et al (2015), Raz and Levin (2014) RGVP tracking performance, most have focused on certain RGVP subregions of interest, for example, the optic nerve, the optic tract, and/or the RGVP fibers within the optic chiasm (as summarized in et al, 2020a;Zhang, Xie, et al, 2020). A comprehensive quantitative and visual comparison is performed using dMRI data from the Human Connectome Project (HCP; Glasser et al, 2013;Van Essen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 gives a summary of existing tractography-based RGVP studies to describe the current state of the art in terms of the fiber tracking methods being used, among which the standard diffusion tensor imaging (DTI) tractography and more advanced methods such as those using constrained spherical deconvolution (CSD) and generalized Q-sampling imaging (GQI) are most widely used. While these studies have shown highly promising T A B L E 1 Summary of published tractography studies of the RGVP and its subregions, organized according to the fiber reconstruction methods employed and the anatomical region studied OT Backner et al (2018), Frezzotti, Giorgio, Toto, De Leucio, andDe Stefano (2016), Glick-Shames, Backner, Bick, Raz, and Levin (2019), Hoffmann et al (2012), Levin, Dumoulin, Winawer, Dougherty, and Wandell (2010), Malania, Konrad, Jägle, Werner, and Greenlee (2017), Maleki, Becerra, Upadhyay, Burstein, and Borsook (2012), Ogawa et al (2014, Raz, Bick, Klistorner, et al (2015), Raz and Levin (2014) RGVP tracking performance, most have focused on certain RGVP subregions of interest, for example, the optic nerve, the optic tract, and/or the RGVP fibers within the optic chiasm (as summarized in et al, 2020a;Zhang, Xie, et al, 2020). A comprehensive quantitative and visual comparison is performed using dMRI data from the Human Connectome Project (HCP; Glasser et al, 2013;Van Essen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we used the single-shell b=1000 s/mm 2 data, consisting of 90 DW images and 18 baseline images, to perform fiber tracking using each compared tractography method (see Section 2.2 for details). We chose single-shell b=1000 s/mm 2 data because it is similar to clinical acquisition protocols as applied in many previous RGVP-related studies (Altintaş et al, 2017; Attyé et al, 2018; Backner et al, 2018; Burton et al, 2018; de Blank et al, 2013; Frezzotti et al, 2016; Glick-Shames et al, 2019; Hofer et al, 2010; Hofstetter et al, 2019; Jacquesson, Frindel, et al, 2019; Jin et al, 2019; Lober et al, 2012; Malania et al, 2017; Maleki et al, 2012; Ogawa et al, 2014; Noa Raz et al, 2015; Noa Raz & Levin, 2014; Schmidt et al, 2018; Wu et al, 2019). Furthermore, single-shell b=1000 s/mm 2 data has been shown in our previous study to be more effective for identification of cranial nerves than higher b values (Xie et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…This technique dismisses the subjectivity of patients; thus, it is beginning to show promise in evaluating patients with compressive neuropathy ( 2 ). Several studies have shown that mfVEP can predict visual outcome in these patients ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%